Sundry Modernism : Materials for a study of Palestinian Modernism. - Toukan, Oraib (Berlin : Sternberg Press, 2017)
Khoury, Rizek ; Tukan, Jafar ; Karim, Sayed ; Sayegh , Fouad
modernisme in Palestina
boek